A NEW RECORD AND NEW SPECIES OF THE GENUS ACUARIA BREMSER, 1811 (ACUARIIDAE: NEMATODA) FROM SINDH / JUNGLE SAPRROW (PASSERIDAE: PASSERIFORMOES) IN LARKANA, SINDH, PAKISTAN. - I. Chandio; A. M. Dharejo; M. M. Khan (Journal of Animal and Plant Sciences, 2022)
The present study was conducted as part of a PhD project to introduce one of Sindh's bird species and helminthic parasites of Passer pyrrhonotus (Blyth, 1845) were examined from Larkana districts of Sindh Province, Pakistan. During present investigation for the helminthic parasites, total fourteen Passer pyrrhonotus (Sindh Jungle Sparrow) were examined from Larkana districts of Sindh Province, Pakistan. Out of fourteen birds, only one was found infected with five nematodes of genus Acuaria Bremser, 1811 (02♂, 03♀) belonging to Acuariidae: Nematoda, obtained from the intestine of Passer pyrrhonotus, were killed and processed in a 70% ethanol and glycerol solution for comprehensive study. The specimens were compared with the different species of genus Acuaria, reported from different birds around the world. The new species is named as Acuaria pakistanensis n.sp. The name of the new species relates to the name of the country from which it was obtained. However, this genus and host Passer pyrrhonotus (Sindh/ Jungle Sparrow) is reported first time from Pakistan.
Keywords: Acuaria pakistanensis n.sp; Passer pyrrhonotus (Sindh/ Jungle Sparrow); Larkana; Sindh; Pakistan